THE EFFECTS OF TEMPERATURE AND TIME OF PLANT EXTRACTION USING ULTRASONIC METHOD ON ANTIOXIDANT ACTIVITY: SYSTEMATIC REVIEW - Maharani, Salsabila Nanda; Via Rifkia (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2024)
Excessive free radicals can induce oxidative stress and provoke degenerative diseases in human body. Plant extracts such as starfruit (Averrhoa bilimbi L.), guava (Psidium guajava L.), red spinach (Alternanthera amoena voss.), soursop (Annona muricata L.), and cherry (Muntingia calabura L.) harbor natural antioxidants that hold promise for theurapeutic use in these conditions. This study aims to determine the effect of temperature (25°C, 30°C, 35°C, 40°C, 42,5°C, 45°C, 50°C, 55°C, 60°C) and time (10, 20, 30, 45, 60 minutes) of plant extraction using ultrasonic method on antioxidant activity. This study used systematic review method that use evidence-based data to be reviewed, valuated, assessed for quality, and analyzed. There were 5 journals that met the inclusion and exclusion criteria which will be used as data sources for further study. The results showed that the treatment of temperature and extraction time using ultrasonic method have notable impact on the antioxidant activity as the increasing temperature and time of extraction are directly proportional to antioxidant compounds in plant extracts, yet after passing a certain point it begins to decrease due to the excessive exposure, the best extraction temperatures to achieve the highest antioxidant activity are 40°C, 42,5°C, 45°C with extraction time of 20 minutes.